Whole Exome Sequencing Reveals Rare Variants in Genes Associated with Metabolic Disorders in Women with PCOS - Priyal Sharma; Ashutosh Halder; Manish Jain; Manish Tripathi (Journal of Human Reproductive Sciences, 2023)
Background: Polycystic ovary syndrome (PCOS) is a complex genetic trait, the pathogenesis of which is governed by an interplay of genetic and epigenetic factors. However, the aetiology of PCOS is not fully understood. Aims: The objective of this study was to investigate the genetic causes of PCOS by identifying rare variants in genes implicated in its pathophysiology. Settings and Design: This was a hospital-based observational study. Materials and Methods: We used whole-exome sequencing for 52 PCOS women to identify the rare variants in genes related to PCOS pathogenesis. Subsequently, we analysed these variants using in silico prediction software to determine their functional effects. We then assessed the relationship between these variants and the clinical outcomes of the patients. Statistical Analysis Used: Student’s t-test and Fisher’s exact test were used to compare clinical parameters and frequency differences amongst PCOS patients with and without variants. Results: A total of four rare exonic variants in obesity- and hyperinsulinaemia-related genes including UCP1 (p.Thr227Ile), UCP2 (p.Arg88Cys), IRS1 (p.Ser892Gly) and GHRL (p.Leu72Met) were identified in eight patients. Significant differences were observed between the patients carrying variants and those without variants. PCOS patients with identified variants exhibited significantly higher average body mass index and fasting insulin levels of PCOS subjects with identified variants compared to those without variants (P < 0.05). Additionally, there were significant differences in the variant frequencies of four variants when compared to the population database (P < 0.05). Conclusion: This study shows a prevalence of rare variants in obesity and hyperinsulinaemia-related genes in a cohort of PCOS women, thereby underscoring the impact of the identified rare variants on the development of obesity and associated metabolic derangements in PCOS women.